Multi-Stakeholder MSME Collaboration for Economic Resilience: A Systematic Literature Review of Asian Governance - Bahar Buasan; Vita Mayastinasari; Sari Wahyuni; Riani Rachmawati (Research Synergy Foundation, 2026)
The use of multi-stakeholder collaboration is the main focus of Asian MSME development, but the current literature has focused primarily on Western forms of governance with scanty knowledge of the cultural aspects and stakeholder power relations influence the collaboration outcomes in Asian settings. This literature review analyzes the patterns of multi-stakeholder collaboration, stakeholder positioning, and systemic challenges of the Asian MSME development programs. The studies included in the analysis were 54 peer-reviewed articles “20152025” located in SCOPUS based on thematic synthesis and three research questions. The patterns of research indicate that there has been a paradigm change towards integrated frameworks informed by four cultural dimensions, including traditional governance philosophy, religious-spiritual integration, technology-based modernization, and environmental-cultural resilience. Eastern Asia is found to be more interested in technology, South east in community involvement and South Asia in policy innovation. The Power-interest approach finds the gaps in the representation where Government is the only Key Player and the Local Communities, Religious Leaders and International NGO are kept aside yet they play a crucial role in the implementation processes. The systemic issues include power imbalances, institutional fragmentation, resource constraint, and tensions between the traditional and modern business. The review goes beyond Stakeholder and Governance Theory by showing that the Asian MSME collaboration is a cyclical process where cultural legitimacy is input and output based on culturally-grounded protocols.